2012
DOI: 10.4111/kju.2012.53.12.830
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Combined Approach of T1-Weighted, T2-Weighted, Dynamic Contrast-Enhanced, and Diffusion-Weighted Imaging in Prostate Cancer

Abstract: PurposeWe evaluated the value of a combined approach of T1-weighted (T1W) imaging, T2-weighted (T2W) imaging, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), and diffusion-weighted imaging (DWI) for the detection of prostate cancer and extracapsular extension (ECE) in patients with prostate cancer by using pathologic data after radical prostatectomy.Materials and MethodsFrom April 2009 to December 2011, 126 patients who underwent radical prostatectomy and prostate MRI for prostate cancer were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…a At mpMRI (multiparametric magnetic resonance imaging). This result is in line to previous studies [10][11][12][18][19][20], suggesting that this nomogram could be of help to confirm results from standard T2-WI, which is currently recognized as the most accurate sequence to detect macroscopic ECE.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…a At mpMRI (multiparametric magnetic resonance imaging). This result is in line to previous studies [10][11][12][18][19][20], suggesting that this nomogram could be of help to confirm results from standard T2-WI, which is currently recognized as the most accurate sequence to detect macroscopic ECE.…”
Section: Discussionsupporting
confidence: 94%
“…Although T2-WI has some limitations (long acquisition times and susceptibility to motion artefacts), with the possibility of an impaired image quality, ADC from DWI is associated with high sensitivity to detect ECE [10][11][12][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 There are several guidelines from the European Association In detecting lymph node metastasis, mp-MRI showed a high specificity of 91%-97% but a low sensitivity of 14%-36%. 10,11,27 Hövels et al 12 20 .…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that nodal imaging studies should only be recommended for patients having a probability of 45% or higher for LNI. Min et al 11 We stratified the cohorts into 3 groups according to the number of LNE: no significant LNE group, one LNE group, and more than 2 LNE group. Each group was graded as 0, 1, and…”
Section: Introductionmentioning
confidence: 99%